Assessment Effective Factors on Clinical Application of Nursing Continuing Education from the Viewpoints of Nurses - Mohsen Hojat (Journal of Global Pharma Technology, 2017)
Introduction Ongoing continuing education program with the present methods and conditions is inadequately helpful and applicable. There are various factors, which influence the efficiency and efficacy of such programs for nurses. The present study aimed to investigate the effective factors in application of continuing education from the viewpoints of nurses. Methods This is a cross- sectional descriptive study. Sampling was census, conducted on nurses in Jahrom, Iran in autumn 2015. Data were collected by Dehghan Nayeri and Khosravi checklist with reliability of α=0.949. Data were analyzed by descriptive statistical tests (frequency distribution and mean), independent t- tests and Spearman correlation coefficient. Results In the present study, 176 subjects were recruited of whom 72.7% were female. Subjects' mean age was 21.64 (14.18) years. From the viewpoints of the nurses, the most effective factors for application of continuing clinical education were